2007
DOI: 10.1210/jc.2006-2846
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Insulin-Like Growth Factor Stimulation of Vascular Endothelial Growth Factor Production by Luteinized Granulosa Cells: Comparison between Polycystic Ovarian Syndrome (PCOS) and Non-PCOS Women

Abstract: Insulin and IGFs promote VEGF-A production in LGCs, but the response patterns are different when cells from PCOS and non-PCOS women are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 25 publications
4
29
1
Order By: Relevance
“…These findings are compatible with the concept that VEGF through the stimulation of ovarian angiogenesis may be a key mediator of OHSS (90). The observed reduction of VEGF levels may significantly rely upon the insulinlowering effect of metformin since insulin stimulates VEGF production by cultured luteinized granulosa cells from women with and without PCOS (91).…”
Section: Metformin In Pcossupporting
confidence: 87%
“…These findings are compatible with the concept that VEGF through the stimulation of ovarian angiogenesis may be a key mediator of OHSS (90). The observed reduction of VEGF levels may significantly rely upon the insulinlowering effect of metformin since insulin stimulates VEGF production by cultured luteinized granulosa cells from women with and without PCOS (91).…”
Section: Metformin In Pcossupporting
confidence: 87%
“…Given the known anti-angiogenic nature of TSP-1, it is probable that the inability of follicles overexpressing TSP-1 to reach maturation results from inadequate local vascular development. Since IGF-1 signalling promotes vascularization through increased VEGF expression in the developing follicle [23] and elsewhere [34,35], our findings suggest an intriguing mechanism for suppressing TSP-1 in order to favour angiogenesis in this context. Since TSP-1 directly modulates endothelial responses, and is also involved in the LRP-1-dependent clearance of VEGF [20], transient TSP-1 suppression in response to IGF-1 may represent another mechanism by which the follicle becomes cyclically proangiogenic at key developmental stages.…”
Section: Discussionmentioning
confidence: 74%
“…Our finding is in disagreement with Agrawal et al (2002 (4) , Artini et al (2006) (20) , Artini et al (2009) (21) and Mary et al (2016) (22) who found elevated levels of VEGF in serum and follicular fluid of patients with PCOS undergoing IVF. The increased levels of VEGF explained by the finding that the release of VEGF by granulosa lutein cells is augmented by insulin (4,23) and that luteinized granulose cells in women with PCOS are more sensitive to insulin (23) . Since many women with PCOS have hyperinsulinemia, hypersecretion of VEGF in women with PCOS may be due to hyperinsulinemia (24) , whereas Lee et al (25) explained the high levels of VEGF by the investigation of single nucleotide polymorphisms of VEGF gene, in 134 Korean women with PCOS and they concluded that the single nucleotide polymorphisms regulating the expression and activity of VEGF may be significantly associated with pathogenesis of PCOS.…”
Section: Discussion:-mentioning
confidence: 99%